Metal-organic frameworks for selective capture of volatile organic compounds containing carboxylic acid functional groups and / or volatile alcohols
A MOF constructed from trimers of metal octahedrons with organic polycarboxylate linkers addresses the challenge of selective VOC capture in humid conditions, enhancing adsorption of carboxylic acid and hydroxyl functional groups for improved air purification and art preservation.
Patent Information
- Application Number
- JP2024534695
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-10
- Filing Date
- 2022-12-02
- Publication Date
- 2024-12-26
AI Technical Summary
Existing metal-organic frameworks (MOFs) are ineffective in selectively capturing volatile organic compounds (VOCs) containing carboxylic acid and hydroxyl functional groups, especially in humid environments, due to competitive adsorption with water, which limits their effectiveness in applications like air purification and art preservation.
The development of a specific MOF constructed from trimers of metal octahedrons interconnected by organic polycarboxylate linkers, featuring Lewis acid sites, which enhances the selective adsorption of VOCs containing carboxylic acid and hydroxyl functional groups even in humid conditions.
This MOF effectively adsorbs VOCs containing carboxylic acid and hydroxyl functional groups in humid environments, maintaining high adsorption capacity and selectivity, thus improving air purification systems and art preservation methods.
Smart Images

Figure 2024546797000006 
Figure 2024546797000007 
Figure 2024546797000008
Abstract
Description
[Technical field]
[0001] The present invention relates inter alia to the use of porous crystalline solids composed of metal-organic frameworks (MOFs) for the selective capture of volatile organic compounds (VOCs) containing carboxylic acid functional groups and / or volatile organic compounds (VOCs) containing hydroxyl functional groups.
[0002] The MOF solid of the present invention can be used for air purification, for example, selective capture of VOCs containing carboxylic acid functional groups and / or volatile organic compounds (VOCs) containing hydroxyl functional groups from outside air. It can be used for art conservation, such as the conservation of cellulose derivative films, for indoor air purification systems, such as HEPA air filters, sorbent purifiers, kettle filters, fet filters, honeycomb filters or air conditioning filters, for outdoor air purification systems, such as gas masks, nose filters, adsorption columns or chimney filters, and in cosmetic applications, such as deodorants, odor control shampoos, hygiene protection products, wipes or diapers.
[0003] The references in square brackets [X] refer to the list of references at the end of the examples. [Background technology]
[0004] Cultural traditions can be defined as a set of tangible objects such as monuments, architectural structures, sculptures, paintings, films, and archaeological sites, as well as traditions or life expressions inherited from ancestors and transmitted to descendants [1]. One of the more recent tangible artifacts in cultural traditions is the cellulose derivative film. In the last 50 years, it has become clear that the chemical stability of these materials represents a major concern due to the spontaneous chemical degradation of cellulose triacetate, which leads to deacetylation and chain scission of the polymer, causing a specific type of decomposition known as the "vinegar syndrome", characterized by a vinegar-like odor emitted from the artifacts. This odor results from the emission of the VOC acetic acid, one of the main pollutants in museums.
[0005] It is generally accepted that polar VOCs containing carboxylic acid functional groups are significant pollutants in vehicles, museums, and archives. In museums, for example, these VOCs need to be controlled, as reported, for example, in N. Blades et al., Guidelines on Pollution Control in Heritage Building, The Council For Museums, Archives And Libraries, London, 2000[2]. For example, D. Thickett et al.in Met.98 Proc.Int.Conf.Met.Conserv.(Eds.:W.Mourey,L.Robbiola),James&James,London,1998,pp.260-264[3], and V.Kontozova et al.in Proc.art2002 7th Int.Conf.Nondestruct.Test.Microanal.Diagnostics Conserv.Cult.Environ.Herit.(Eds.:R.Van Grieken,K.Janssens,L.Van't dack,G.Meersman),University Of Antwerp,Antwerp,2002[4],Schieweck A,et al.,in J Cult Herit.2011[5], and Al Mohtar et al. in Sci. As reported in Rep. 2021[6], the preservation of cultural traditions in museums and historical buildings in fact depends on the limitation of acetic acid contamination in indoor air and in indoor showcases. This volatile organic pollutant reduces the degree of polymerization of cellulose in paper, corrodes lead-containing alloys and other metals, and deteriorates calcareous materials (stone, ceramics), as disclosed for example in B. Krupinska, et al., Microchem. J. 2013, 110, 350[7] and Brokerhof, AW et al., in James&James (Science Publishers), London, 1996[8], Tetreault et al., in Studies in Conservation, 2003, 48(4)[9].It can easily form from wood deterioration, as reported in L.T. Gibson et al., Corros. Sci. 2010, 52, 172
[10] . Complete elimination of the source is therefore often difficult, if not impossible, and periodic monitoring of the acetic acid concentration in the air has been proposed, for example, as reported in T. Prosek et al., Corros. Sci. 2014, 87, 376
[11] . Very low maximum average concentrations of acetic acid of 400 ppb and 40 ppb for 1-year and 100-year preservation goals, respectively, for museums, galleries, libraries, and archival collections have been proposed by the American Society of Heating Refrigeration and Air Conditioning Engineers, in Heating, Vent. Air-Conditioning Appl., ASHRAE, Atlanta, 2003
[12] .
[0006] One option for its removal is the use of sorbent materials in museums. Traditional sorbents such as zeolites and activated carbon have been much applied to capture volatile organic compounds. However, acetic acid poses an additional challenge compared to other less acidic compounds due to competitive adsorption of water under normal humidity conditions of cultural artifact storage. Zeolites can have very polar surfaces to strongly interact with acetic acid, but are easily saturated with water at very low humidity levels, as reported in MLP Into, et al., Adsorption 2003, 9, 303
[13] . In contrast, activated carbon is usually more hydrophobic than zeolites and is not saturated with water under normal relative humidity conditions (<60%)
[14] , but does not bind acetic acid as strongly.
[0007] Metal-organic frameworks are a versatile class of porous hybrid crystalline structures developed in the past decades, made from the association of inorganic moieties with polycomplexing organic linkers to form micro- or mesoporous materials whose pore size, shape, surface area and hydrophilic / hydrophobic balance can be tailored for a wide range of potential applications. In the field of adsorption, they are used to bind polar or quadrupolar molecules, e.g. CO, NO or CO, to enhance selectivity towards more inert species (e.g. alkanes). 2 One can underline the advantages of MOFs that exhibit active sites such as Lewis, Brönsted or redox or functional polar or non-polar groups from organic linkers that specifically interact with VOCs. However, no MOFs have yet been reported for highly efficient and selective capture of VOCs containing carboxylic acid functional groups in wet environments, without the need to repel water by the use of hydrophobic materials. Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, there remains a need to find a stable means for selectively capturing VOCs containing carboxylic acid and / or hydroxyl functional groups from indoor air in vehicles, museums and archives, especially in humid environments, that outperforms all previously reported and allows the preservation of cultural heritage. [Means for solving the problem]
[0009] To address this need, extensive research has been conducted by the inventors to find specific MOFs that can highly efficiently and selectively adsorb VOCs containing carboxylic acid functional groups and / or VOCs containing hydroxyl functional groups, even in humid environments found, for example, in rooms within buildings, where the relative humidity is typically around 40%-60%.
[0010] Before turning to the description of the invention itself, certain terms and phrases will now be defined in order to facilitate understanding of the invention. · When used herein except in the claims, the terms "a", "an", "the", and / or "said" mean one or more. When used herein in the claims, when used with the words "comprise", "comprises", and / or "comprising", the words "a", "an", "the", and / or "said" may mean one or more. When used herein and in the claims, the terms "having", "has", "is", "have", "including", "includes", and / or "include" have the same meaning as "comprising", "comprises", and "comprise". When used herein and in the claims, "another" may mean at least a second, or more. As used in this specification and claims, "about" refers to any inherent measurement error or rounding of a value (e.g., a measurement, calculation of a ratio, etc.), and thus the term "about" may be used with any value and / or range. · Phrases such as "combinations thereof," "mixtures thereof," following a list, the use of "and / or" as part of a list, the recitation of tables, the use of "such as" as part of a list, the phrase "for example," and / or parenthetical listings with "for example," i.e., any combination (e.g., any subset) of the set of listed components, as well as combinations and / or mixtures of related species and / or embodiments described herein, although not directly located in such a list, are also contemplated. Such related and / or similar genera, subgenera, species and / or embodiments described herein are contemplated both in the form of individual components that may be claimed, as well as mixtures and / or combinations that may be described in the claims as "at least one selected from," "mixtures thereof," and / or "combinations thereof." In general, the term "substituted," whether preceded by the term "optionally" or not, substituents contained in the formulas of this invention refer to the replacement of hydrogen radicals in a given structure with the radical of a specified substituent. When more than one position in any given structure may be substituted with more than one substituent selected from a specified group, the substituents may be the same or different at all positions. As used herein, the term "substituted" is considered to include all permissible substituents of organic compounds. As used herein, the term "about" can refer to a variation of ±5%, ±10%, ±20%, or ±25% of the specified value. For example, "about 50" percent can have a variation of 45-55% in some embodiments. In the case of integer ranges, the term "about" can include one or two integers greater than and / or less than the recited integer. Unless otherwise indicated herein, the term "about" is intended to include values, e.g., concentration values, near the recited range that are equivalent with respect to the functionality, composition, or embodiment of the individual components. As used herein, the term "and / or" means any one of the items, any combination of the items, or all of the items with which this term is associated. As will be appreciated by those of skill in the art, all numbers, including those expressing quantities of ingredients, properties such as cavity / pore size and BET specific surface area, reaction conditions, and the like, are approximate and are understood to be optionally modified in all instances by the term "about." These values may vary depending on the desired properties one of skill in the art seeks to obtain utilizing the teachings of the description herein. It is also understood that such values inherently contain variability necessarily resulting from the standard deviation found in their respective testing measurements. · As will be understood by those skilled in the art, for any and all purposes, particularly with respect to providing a written description, all ranges recited herein also encompass any and all possible subranges and combinations of subranges, as well as the individual values, particularly integer values, that make up the ranges. The recited ranges include each specific value, integer, decimal, or identity within the range. Any recited range can be readily recognized as fully descriptive and allowing for division of the same range into at least equal halves, thirds, quarters, fifths, or tenths. As a non-limiting example, each range described herein can be readily broken down into a lower third, a middle third, an upper third, and so on. Those skilled in the art will readily recognize that when members are grouped together in a common manner, such as in a Markush group, the invention encompasses not only the entire group recited as a whole, but also each member of the group and all possible subgroups of the main group. Moreover, for all purposes, the invention encompasses not only the main group, but also the main group in which one or more of the group members are absent. Thus, the invention contemplates the explicit exclusion of any one or more of the recited group members. Thus, the provision may be applied to any of the disclosed categories or embodiments, whereby any one or more of the recited elements, species, or embodiments may be excluded from such category or embodiment, e.g., as used in an express negative limitation. As used herein, the expression "three-dimensional structure" is understood to mean a three-dimensional arrangement or repetition of units or moiety variants, which may also be characterized as "organometallic polymers", as conventionally understood in the field of MOF materials. As used herein, the term "solid" refers to any type of crystalline material. The solid may be, for example, in the form of crystals, powders or particles of various morphologies, for example, spherical, lamellar, etc. The particles may be in the form of nanoparticles. · As used herein, "humid environment" means an atmospheric environment that contains water vapor. It may be air that contains water vapor. The amount of water vapor present in an environment, e.g., air, increases as temperature increases. The difference in the amount of water vapor in the air may be very large. For example, a parcel of air close to saturation (e.g., about 100% relative humidity) may contain 28 grams of water per cubic meter of air at 30°C, but only 8 grams of water per cubic meter of air at 8°C. Water vapor or steam or aqueous vapor is the gaseous phase of water. It is one state of water in the hydrosphere. Under typical atmospheric conditions, water vapor is continuously generated by evaporation and removed by condensation. The vapor content of air can be measured using a device known as a hygrometer. In the present invention, the amount of water vapor in an environment, e.g., air, may range from dry air to saturation, e.g., 10 to 30°C, at room temperature, i.e., at a temperature between 18°C and 28°C. ·MOFs are constructed from bridging organic ligands, also called "linkers" or "linkers" or "spacers" or "spacers", that remain intact throughout the synthesis and act as linkers in the network of the resulting MOF structure. As used herein, the term "ligand" or "linker" or "spacer" refers to a ligand coordinated to at least two metals, providing distance between these metals and participating in the formation of an empty space or pore, also called the "core", within the MOF. · As used herein, "aliphatic" refers to acyclic or cyclic, saturated or unsaturated carbon compounds, excluding aromatic compounds (IUPAC). Open-chain compounds that do not contain any kind of ring, whether linear or branched, are always aliphatic. Cyclic compounds can be aliphatic if they are not aromatic. Aliphatic compounds can be saturated, bonded by single bonds (alkanes), or unsaturated with double bonds (alkenes) or triple bonds (alkynes). Besides hydrogen, other elements can be bonded to the carbon chain, most commonly oxygen, nitrogen, sulfur, and chlorine. As used herein, "aromatic" refers to a cyclic conjugated molecular entity that has a stability (due to delocalization) significantly greater than that of a hypothetical localized structure (e.g., the Kekulé structure) that is said to possess aromaticity. The use of this term is based on application of the Hückel (4n+2) rule and consideration of the topology of orbital overlap in the transition state (IUPAC).
[0011] The inventors have shown through the present invention that by using a specific selection of MOFs constructed from trimers of metal octahedra and containing Lewis acid sites interconnected by organic polycarboxylate linkers, it is possible to strongly enhance the selective capture of VOCs containing carboxylic acid functional groups and / or VOCs containing hydroxyl functional groups, even in humid environments typically found, for example, in buildings.
[0012] In particular, the present invention relates to the use of at least one porous metal-organic framework (MOF) material for selective adsorption of volatile organic compounds from a gaseous environment such as air, said volatile organic compounds comprising at least one carboxylic acid group and / or said volatile organic compounds comprising hydroxyl functional groups, said MOF material being constructed from trimers of metal octahedra and comprising at least 1 mmol / g of Lewis acid sites interconnected by organic polycarboxylate linkers. In a preferred embodiment, the present invention relates to the use of at least one porous metal-organic framework (MOF) material for selective adsorption of volatile organic compounds from a gaseous environment such as air, said volatile organic compounds comprising at least one carboxylic acid group and said MOF material being constructed from trimers of metal octahedra and comprising at least 1 mmol / g of Lewis acid sites interconnected by organic polycarboxylate linkers.
[0013] The present invention also relates to a method for selective adsorption of organic volatile compounds from a gaseous environment, comprising the step of contacting at least one metal-organic framework (MOF) material with a gaseous environment volume comprising an organic volatile compound, said volatile organic compound comprising at least one carboxylic acid group and / or said volatile organic compound comprising a hydroxyl functional group, said MOF material being constructed from trimers of metal octahedra and comprising at least 1 mmol / g of Lewis acid sites interconnected by organic polycarboxylate ligands. Preferably, the present invention also relates to a method for selective adsorption of organic volatile compounds from a gaseous environment, comprising the step of contacting at least one metal-organic framework (MOF) material with a gaseous environment volume comprising an organic volatile compound, said volatile organic compound comprising at least one carboxylic acid group and said MOF material being constructed from trimers of metal octahedra and comprising at least 1 mmol / g of Lewis acid sites interconnected by organic polycarboxylate ligands.
[0014] "Lewis acid sites built from trimers of metal octahedra", by an element capable of accepting a pair of non-bonding electrons from another substance. In trimer-based MOF structures, three coordinated metals share one central μ3-oxo forming a trimer with six ligands and three terminal ligands that act as linkers in the structure, completing the metal coordination sphere, one HO- and two water molecules with Lewis acid sites that are effective in removing the terminal water ligands. In the use according to the invention, the carboxylate from the VOC replaces the terminal water ligand, resulting in a stronger Lewis acid site-VOC interaction, see Figure 1 (hydrogen atoms omitted for clarity). The amount of Lewis acid sites with reference to publications related to these values can be found in references
[31] for MIL-100(Fe),
[32] for MIL-100(Al),
[33] for MIL-127(Fe) and
[34] for MIL-101(Cr). JACS 2006
[44] describes a method for determining the number of Lewis acid sites.
[0015] Advantageously, according to the invention, the MOF has a p / p of less than 0.4 for the water adsorption isotherm at 30° C. 0 The MOF can adsorb more than 50% of its total adsorption capacity at relative pressure. Water adsorption isotherms at 30° C. can be measured in millimoles per gram of sample using volumetric or gravimetric adsorption equipment, preferably gravimetric adsorption equipment, typically from low pressure up to atmospheric pressure of about 1 bar.
[0016] Advantageously, according to the invention, the metal centre of the MOF material may be chosen from Fe, Al, Ti, Mn, V, Sc, Mn, Cr and mixtures thereof, preferably Fe, Al and mixtures thereof.
[0017] Advantageously, according to the invention, the MOF material may comprise Lewis acid sites constructed from trimers of metal octahedra and interconnected by organic polycarboxylate linkers in a concentration of at least 1 mmol / g, preferably at least 1.5 mmol / g, more preferably at least 2 mmol / g or at least 2.5 mmol / g. Preferably, the Lewis acid sites constructed from trimers of metal octahedra and interconnected by organic polycarboxylate linkers are chemically accessible. By "chemically accessible" is meant available sites where a Lewis acid-base reaction can take place.
[0018] Advantageously, according to the invention, the MOF material has a molecular weight of 50 m 2 / g, preferably 100m 2 The specific surface area of the MOF material can be determined by the N 2 It can be evaluated using the BET model from the isotherm.
[0019] Advantageously, according to the invention, the MOF material has an average pore size of at least 0.5 nm. The average pore size can be measured using the crystallographic information file (CIF) of said MOF. It can also be calculated from the nitrogen isotherm, for example by applying mathematical equations such as the BJH (Barret-Joyner-Halenda), DFT (density functional theory), Horvath-Hawazoe or Dubinin-Astakhov methods, which allow the average pore size distribution to be determined.
[0020] Advantageously, according to the invention, the organic polycarboxylate linker of the MOF may be chosen from di-, tri- or tetracarboxylic acids. Preferably, the organic polycarboxylate linker of the MOF is Halo groups (such as -Cl or -Br), -OH, -NH 2 and -NO 2 C may have one or more substituents selected from 6 ~C 24 Aromatic polycarboxylate linkers, such as benzyl or naphthyl di-, tri- or tetracarboxylates, and Halo groups (such as -Cl or -Br), -OH, -NH 2 and -NO 2 C optionally having one or more substituents selected from 4 ~C 16 The linker may be selected from polycarboxylate aliphatic linkers.
[0021] Advantageously, each of the aforementioned linkers preferably comprises a non-polar fluorinated group and / or a non-polar C, which are grafted directly onto the linker and point into the pores of the MOF. 1 ~C 20 It may be one that has no groups.
[0022] Advantageously, according to the invention, C 6 ~C 24Aromatic polycarboxylate linkers include terephthalate, 1H-pyrazole-3,5-dicarboxylate, 2,5-furandicarboxylate, naphthalene-2,6-dicarboxylate, biphenyl-4,4'-dicarboxylate, benzene-1,2,4-tricarboxylate, benzene-1,3,5-tricarboxylate, benzene-1,3,5-tribenzoate, benzene-1,2,4,5-tetracarboxylate, 3,3',5,5'-tetracarboxylate diphenylmethane, naphthalene-2,3,6,7-tetracarboxylate, naphthalene-1,4,5,8-tetracarboxylate, biphenyl-3,5,3 The compound may be selected from azobenzene-4,4'-tetracarboxylate, 2-chloroterephthalate, 2-bromoterephthalate, azobenzenedicarboxylate, azobenzenetetracarboxylate, 2,5-thiophenedicarboxylate, 2-aminoterephthalate, 2-nitroterephthalate, 2,5-dihydroxyterephthalate, 2,5-pyrazinedicarboxylate, azobenzene-4,4'-dicarboxylate, 3,3'-dichloro-azobenzene-4,4'-dicarboxylate, 3,3'-dihydroxy-azobenzene-4,4'-dicarboxylate, 3,5,3',5'-azobenzenetetracarboxylate and mixtures thereof.
[0023] Advantageously, according to the invention, C 4 ~C 16 The polycarboxylate aliphatic linker can be an alkyl linker. 4 ~C 16 The polycarboxylate alkyl linker may be selected from di-, tri-, or tetracarboxylate or carboxylic acid linkers such as fumarates, succinates, glutarates, muconates, adipates, and mixtures thereof.
[0024] Advantageously, according to the invention, the MOF material is selected from the group consisting of MIL-88A(Fe), MIL-88B(X)(Fe), where X is Br, NH 2 , Cl, NO 2, 2OH and COOH
[14] ) and mixtures thereof, more preferably selected from MIL-100(Fe,Al)[15,16], MIL-127(Fe)
[17] and mixtures thereof.
[0025] The use according to the invention can be an air quality application and / or a cosmetic application. Fine art conservation, such as the preservation of cellulose derivative films (its degradation compounds catalyze the hydrolysis and oxidation of cellulose and cellulose ethers, meaning that acetic acid has an autocatalytic effect on cellulose-based artifact degradation. One way to control the integral loss of these artifacts is the removal of VOCs from museum storage / exhibits [18-20]), Indoor air purification systems such as HEPA air filters, adsorbent purifiers, kettle filters, fet filters, honeycomb filters or air conditioning filters, Outdoor air purification systems such as gas masks, nasal filters, adsorption columns or chimney filters, Cosmetic applications such as deodorants, anti-odor shampoos, hygiene protection products, wipes or diapers.
[0026] Advantageously, according to the invention, the gaseous environment may be air. The gaseous environment may be a humid environment, such as that found in an interior room of a building, which may have a relative humidity of 20% to 80%, preferably 40% to 60%. The gaseous environment may have a temperature of 10 to 180°C, preferably 15 to 100°C, more preferably 15 to 50°C.
[0027] According to the invention, volatile organic compounds containing a carboxylic acid function are volatile organic compounds (VOCs) which have a vapour pressure of 0.01 kPa or more at 293.15 K or have a corresponding volatility under the specified conditions of use. For the purposes of this Directive, fractions of creosote above this value of vapour pressure at 293.15 K shall be considered as VOCs (Council Directive 1999 / 13 / EC of 11 March 1999
[44] ). VOCs containing carboxylic acid functional groups that may be selectively adsorbed in accordance with the present invention may be selected from, for example, acetic acid, formic acid, acrylic acid, propionic acid, isovaleric acid, propiolic acid, butyric acid, isobutyric acid, crotonic acid, methacrylic acid, diacetic acid, butynedioic acid, valeric acid, 2-methylbutanoic acid, pivalic acid, hexanoic acid, 2,3-trimethylbutanoic acid, 3-methylhexanoic acid, 2-ethyl-2-methylbutanoic acid, 3-ethylpentanoic acid, 3,3-dimethylpentanoic acid, 2,4-dimethylpentanoic acid, 2,3-dimethylpentanoic acid, 2-methylbutanoic acid, and mixtures thereof.
[0028] According to the invention, volatile organic compounds containing hydroxyl functions are volatile organic compounds (VOCs) which have a vapour pressure of 0.01 kPa or more at 293.15 K or have a corresponding volatility under the specified conditions of use. For the purposes of this Directive, the fractions of creosote which exceed this value of vapour pressure at 293.15 K shall be considered as VOCs (Council Directive 1999 / 13 / EC of 11 March 1999
[44] ). VOCs containing hydroxyl functions which can be selectively adsorbed according to the invention are monoalcohols, linear, branched or cyclic C 1 ~C 10 They may be selected from monoalcohols and mixtures thereof. They may be selected from methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, pentanol, isopentanol, hexanol, isohexanol, and mixtures thereof.
[0029] Those volatile organic compounds containing carboxylic acid functional groups can be selectively adsorbed in accordance with the present invention, even in humid environments, well above the 40% relative humidity found in museums, as shown in the examples below.Those volatile organic compounds containing hydroxyl functional groups can be selectively adsorbed in accordance with the present invention, even in humid environments, well above the 40% relative humidity found in museums, as shown in the examples below.
[0030] According to the invention, volatile organic compounds containing carboxylic acid functional groups may be present in a gaseous environment (preferably air) at a concentration of at least 40 ppb, preferably at least 400 ppb, more preferably at least 1 ppm. According to the invention, volatile organic compounds containing hydroxyl functional groups may be present in a gaseous environment (preferably air) at a concentration of at least 40 ppb, preferably at least 400 ppb, more preferably at least 1 ppm.
[0031] According to the invention, the MOFs are preferably in a form that allows a large exchange surface between the MOFs and the environment in which the polar volatile organic compounds must be captured by adsorption. The MOFs can be in the form of a composite, embedded for example in the form of powders, granules, pellets, extrudates, monoliths, foam materials, polymers or fibers, or coated on the surface of a polymer material, a paper sheet, a fiber or a metal. For example, the document WO 2009 / 123484
[23] published in October 2009 discloses a useful process for producing a polyurethane foam filter material with adsorption capacity that can be used to support MOFs to implement the invention. Another example is the electropinning of polymers containing MOF particles, disclosed in the literature by M. Rose et al. Adv. Eng. Mater. 2011, 13, 356-360
[24] , R. Ostermann at al. Chem. Commun. 2011, 47, 442-444
[25] , J. Ren et al. Int. J. Hydrogen Energy 2015, 40, 9382-9387
[26] and MRKhan et al. J. Mater. Eng. Perform. 2016, 25, 1276-1283
[27] , which gives a final composite fiber material containing supported MOFs, simplifying the application of MOFs for the adsorption of volatile organic compounds. Other examples could include the use of MOFs with different shapes, such as in the form of granules by coating certain supports, as for example already disclosed in the literature, Valekar et al., RSC Adv, 2017
[28] , or pellets, Q. Ren, et al., " Chem. Eng. J.,, 2015
[29] , or as disclosed in Gkaniatsou et al., Nano Energy, 2020
[30] .
[0032] According to the invention, at least one MOF material or at least one MOF in the form described in the previous paragraph may be comprised in an apparatus selected from an air purifier, a sensor, an adsorption column, a filter, a respirator, an adsorption tower, a hygiene protection product, a wipe or a diaper.
[0033] The present invention advantageously allows low concentrations of VOCs containing carboxylic acid functional groups and / or VOCs containing hydroxyl functional groups to be easily and selectively removed from indoor air, even in the presence of water in the atmosphere / environment, for example in museums which cause serious conservation problems. The present invention advantageously allows low concentrations of VOCs containing carboxylic acid functional groups and / or VOCs containing hydroxyl functional groups to be easily and selectively removed from outdoor air, even in the presence of water in the atmosphere / environment, independent of geographical location, for example through outdoor air purification systems such as gas masks, nose filters, adsorption columns or chimney filters. The present invention advantageously allows easy and selective removal of low concentrations of odorous VOCs containing carboxylic acid functional groups and / or VOCs containing hydroxyl functional groups, for example odor molecules, using deodorants, odor control shampoos, hygiene protection products, wipes or diapers, even in the presence of water in the atmosphere / environment. The following experiments and results confirm the advantages of the present invention over the prior art solutions.
[0034] The following representative examples and figures are intended to help illustrate the present invention and are not intended to limit the scope of the present invention and should not be construed as such. Indeed, in addition to those shown and described herein, various modifications of the present invention and many further embodiments thereof will become apparent to those skilled in the art from the entire contents of this document, including the following examples and references to the scientific and patent literature cited herein. It should be further understood that the contents of these cited references are incorporated herein by reference to help illustrate the state of the art.
[0035] The following examples contain important additional information, illustrations and guidance that can be adapted to the practice of the present invention in its various embodiments and equivalents. MOFs with different amounts of Lewis acid sites are presented: MIL-100(Fe), 3.6 mmol / g iron(III) Lewis acid sites
[31] , MIL-100(Al), 2.2 mmol / g aluminum(III) Lewis acid sites
[32] , MIL-127(Fe), 2.7 mmol / g iron(III) Lewis acid sites
[33] , and MIL-101(Cr), less than 1 mmol / g chromium(III) Lewis acid sites
[34] . MIL-100(Fe) and MIL-100(Al) have an affinity for water and p / p 0 <0.4, reaching half of their total water retention capacity (0.35 p / p for MIL-100(Fe) 0 for MIL-100(Al)
[35] it is about 17.5 mmol / g, and for MIL-100(Al)
[35] it is 0.24 p / p 0 (approximately 13 mmol / g at 25°C, all at 25°C). MIL-101(Cr) shows a lower affinity for water than the last one, with half the capacity at p / p 0 <0.5 is obtained
[36] . [Brief description of the drawings]
[0036] [Figure 1] It represents a metal trimer. Each metal is hexa-coordinated by six oxygen atoms forming an octahedral environment (four oxygen atoms from the building ligands, one central μ3-oxo and one oxygen atom from the terminal ligand). The three coordinated metals share one central μ3-oxo forming a trimer with three terminal ligands, one HO- and two water molecules (hydrogen atoms omitted for clarity). The Lewis acid site is effective in removing the terminal water ligand. In the present invention, the carboxylate from the VOC replaces the terminal water ligand, resulting in a stronger Lewis acid site-VOC interaction. [Figure 2A] Figure 1 shows the nitrogen adsorption isotherm obtained for MIL-100(Fe) (primary vacuum, 150°C for 15 hours). The obtained surface area is approximately 1850 m2.g-1 (assessed using the BET model). [Figure 2B] Figure 1 shows the nitrogen adsorption isotherm obtained for MIL-100(Al) (primary vacuum, evacuated at 150°C for 15 hours). The obtained surface area is approximately 1000 m2.g-1 (assessed using the BET model). [Figure 2C] Figure 1 shows the nitrogen adsorption isotherm obtained for MIL-127(Fe) (primary vacuum, evacuated at 200°C for 3 hours). The obtained surface area is approximately 1400 m2.g-1 (assessed using the BET model). [Figure 2D] Figure 1 shows the nitrogen adsorption isotherm obtained for MIL-101(Cr) (vacuum stripping under primary vacuum at 220°C for 15 hours). The resulting surface area is approximately 2700 m2.g-1 (assessed using the BET model). [Figure 3A] FIG. 1 shows acetic acid adsorption isotherms at T=25° C. for activated (open circles) and non-activated (full squares) MIL-100(Fe). [Figure 3B] 1 shows the acetic acid adsorption isotherm of activated MIL-127(Fe) at T=25° C. [Figure 4] 1 shows the propionic acid adsorption isotherm at T=25° C. for activated MIL-100(Fe). [Diagram 5] 1 shows water adsorption isotherms at 25° C. for activated (open circles) and non-activated (full squares) MIL-100(Fe). [Figure 6A] 13 depicts the acetic acid concentration profile in a closed chamber at 40% RH containing no adsorbent. [Figure 6B] 13 depicts acetic acid concentration profiles in a closed chamber at 40% RH for different MOFs. [Figure 7] 1 shows the TPD spectrum of acetic acid and water (50 / 50% by volume) mixture for MIL-100(Fe). [Figure 8] FIG. 1 shows the TPD spectrum of a mixture of propionic acid and water (50 / 50 volume percent) on MIL-100(Fe). [Figure 9A] Experimental MIL-100(Fe) P-XRD pattern in the 2θ range of 1.6–30° compared with the calculated pattern from the literature.
[37] [Figure 9B]Experimental MIL-100(Al) P-XRD pattern in the 2θ range of 1.6–30° compared with calculated patterns from the literature.
[37] [Figure 9C] The experimental P-XRD pattern of MIL-127(Fe) in the 2θ range of 5–30° is shown, compared with the calculated pattern from the literature. [38, 39] [Figure 9D] Experimental MIL-101(Cr) P-XRD pattern in the 2θ range of 1.6–30° compared with calculated patterns from the literature.
[40] [Figure 10A] Figure 1 shows a thermogravimetric analysis of MIL-100(Fe) under O2 (heating rate 5 °C / min). The thermogravimetric analysis (performed under O2 at 5 °C / min) shows two weight losses: the first one between 25 °C and 250 °C corresponds to the loss of water in the pores of the solid. The second weight loss is due to the degradation of the MOF at about 300 °C. It can be seen that the expected losses are well within the expected range from the literature. [Figure 10B] Figure 1 shows the thermogravimetric analysis of MIL-100(Al) performed under O2 (heating rate 5°C / min). The thermogravimetric analysis (run under O2 at 5°C / min) shows two weight losses: the first one up to 200°C corresponds to the loss of water trapped in the micropores. The second weight loss is due to the degradation of the MOF at about 300°C. This shows that the expected losses are well within the expected range from the literature. [Figure 10C] Figure 1 shows a thermogravimetric analysis of MIL-127(Fe) performed under O2 (heating rate 5°C / min). The thermogravimetric analysis (run under O2 at 5°C / min) shows two weight losses: the first one up to 200°C corresponds to the loss of water trapped in the micropores. The second weight loss is due to degradation of the MOF at about 300°C. This shows that the expected losses are well within the expected range from the literature. [Figure 10D]Figure 1 shows the thermogravimetric analysis of MIL-101(Cr) performed under O2 (heating rate 5°C / min). The thermogravimetric analysis (run under O2 at 5°C / min) shows two weight losses: the first one up to 200°C corresponds to the loss of water trapped in the pores. The second weight is due to the degradation of the MOF at about 300°C. This shows that the expected losses are well within the expected range from the literature. [Figure 11] 1 shows the TPD spectrum of a mixture of formic acid and water (50 / 50 volume percent) for MIL-100(Fe). [Figure 12] 1 shows formic acid adsorption isotherms at 25° C. for activated (open circles) and non-activated (full squares) MIL-100(Fe). [Figure 13] a) Breakthrough curve of acetic acid (500 ppm in N2) over powdered MIL-100(Fe) at 60% relative humidity and (b) the respective isotherms are shown in black and the values obtained from breakthrough are shown in red. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] Working Example According to the present invention, usable MOF materials and their preparation can be further understood by the examples which show some of the processes by which these materials are prepared or used. However, it will be understood that these examples should not be construed as limiting the invention. Variations of the invention, now known or further developed, are considered to be within the scope of the invention described herein and claimed below.
[0038] Example 1: Material synthesis MIL-100(Fe)MOF with 3.6 mmol / g
[31] of iron(III) Lewis acid sites was obtained by ambient pressure synthesis using 0.96 mol of 1,3,5-benzenetricarboxylic acid and 1.42 mol of non-hydrated iron(III) nitrate and 18 L of deionized water, adapted from the conditions mentioned in 1.1. Nouar et al., EP 3357929, 2018
[15] . The mixture is stirred for 62 h at temperatures from 60 °C using a magnetic stirrer. The brown mixture is then filtered to obtain a brown solid, which is washed several times with absolute water and ethanol to remove unreacted 1,3,5-benzenetricarboxylic acid. The powder is then dried at room temperature.
[0039] 1.2.2.2 MIL-100(Al), a MOF with 2 mmol / g
[32] of aluminum (III) Lewis acid sites, 6 mmol of 1,3,5-benzenetricarboxylic acid nonhydrate and 4 mmol of aluminum (III) nitrate are introduced into a 100 mL autoclave. Then, 25 mL of deionized water are added and the mixture is stirred for 10 minutes using a magnetic stirrer, as disclosed in the literature by Marquez et al. Eur J Inorg Chem., 2012, 100 (32)
[16] . The suspension is then placed in a microwave oven and heated to 210 ° C (1 min ramp). The temperature is kept stable for 5 minutes with a power of 1400 W. The mixture is then centrifuged, washed several times with absolute water and ethanol and dried at room temperature.
[0040] MIl-127(Fe), a MOF with 1.3.2.7 mmol / g
[33] of iron(III) Lewis acid sites, was synthesized by adding 2 mmol of NaOH to 4 mL of water, which was then stirred. This solution is then added to 1 mmol of 3,3',5,5'-azobenzenetetracarboxylic acid and 22 mL of pre-stirred isopropanol solution as disclosed in Chevreau et al., CrystEngComm. 2016, 18(22), 4094-4101
[17] . A solution of 2 mmol of iron(III) chloride hexahydrate, prepared with 17 mL of isopropanol, was finally added to the previous solution. The mixture is stirred and gradually heated to 130 °C for 24 h. The reaction mixture is then filtered to obtain a yellow solid, which is washed several times with absolute ethanol and dried at room temperature.
[0041] 1.4. MIL-101(Cr) (counter example), a MOF with less than 1 mmol / g of chromium(III) Lewis acid sites
[34] , was synthesized by adding 12 mmol of benzene-1,4-dicarboxylic acid and 2 mmol of chromium nitrate nonahydrate to a 100 mL autoclave. Then, 25 mL of deionized water is added and the mixture is stirred for 10 min using a magnetic stirrer. The suspension is placed in a microwave oven and heated to 200 °C (4 min ramp). The protocol followed was adapted from Jhung et al, Adv. Mater. 2007
[41] . The temperature is kept stable for 30 min at a power of 1200 W. The mixture is then centrifuged, washed several times with absolute water and ethanol, and dried at room temperature.
[0042] Example 2: Material characterization To confirm the availability of the various materials synthesized in Example 1 above, three series of analyses were performed: Nitrogen adsorption at -196°C; PXRD of synthetic materials; and Thermogravimetric analysis of the synthesized materials.
[0043] 2.1 Nitrogen adsorption at -196 °C: Nitrogen (air-liquid, 99.999%) adsorption-desorption isotherms were measured at -196 °C using a liquid nitrogen cryogenic bath in a volumetric automated device (Micromeritics, ASAP 2010). Prior to the measurements, the samples were outgassed under primary vacuum. The results of all these analyses confirm the porosity of the various materials synthesized in Example 1 and are presented in Figures 2A-D.
[0044] 2.2 PXRD patterns of the synthesized materials: Powder X-ray diffraction patterns were obtained on a Bruker D8-Advance diffractometer using Cu Kα radiation (λ=1.5418 Å). Diffraction patterns were recorded over the 2θ range of 5-70° with a step size of 0.02° and 0.1 seconds per step. The results of all these analyses confirm the acquisition of the various crystalline materials synthesized in Example 1 and are presented in Figures 9A-D.
[0045] 2.3 Thermogravimetric analysis of the synthesized materials: To obtain the TGA profile of each synthesized material, samples (approximately 10 mg) were analyzed with a gravimetric analyzer (Mettler Toledo TGA / DSC 2, STAR system) under air at a constant rate of 5 °C / min. The results of all these analyses confirmed the purity of the various materials synthesized in Example 1 and are presented in Figure 10A-D.
[0046] Example 3: Experiments on the adsorption capacity of different materials 3.1. Protocol used for water sorption measurements Water adsorption isotherms were performed on approximately 50 mg of the material synthesized in Example 1 at 1.0 p / p 0 The adsorption temperature was maintained at 25 °C in a water bath (VMR, VWB2 series, temperature stability 0.2 °C). Prior to the experiments, the material was placed in high vacuum (10 -6 The mixture was activated under 1000 MPa (1.5 mbar) at the desired temperature.
[0047] 3.2. Protocol used for acid vapor sorption measurements The adsorption isotherm was 0.06 p / p for different samples of about 50 mg of the material synthesized in Example 1. 0 The adsorption was measured gravimetrically at low relative pressures up to 1000 MPa. The measurements were performed on a microbalance (CI Electronics) equipped with a pressure sensor (MKS a-BARATRON capacitance manometer in the 100 Torr range). The adsorption temperature was maintained at 25 °C in a water bath (VMR, VWB2 series, temperature stability 0.2 °C). Prior to the measurements, the material was placed in high vacuum (10 -6 The mixture was activated under 1000 MPa (1.5 mbar) at the desired temperature.
[0048] 3.3. Protocol Used for Acetic Acid Adsorption in a Controlled Relative Humidity Environment Approximately 100 mg of material is placed on 10 cm 3 The mixture was placed inside a glass vial and kept in an oven at 100° C. overnight. The vial was removed and tightly closed with a polyethylene cap until use in the experiment. 50 mg of the adsorbent material was weighed (Mettler AE240) into a watch glass and placed in a humidity-controlled glass chamber (2.9 dm 3 The chamber was immediately placed inside a 100-cm-wide 10-cm-long 10-cm-wide 15-cm-long 10-cm-wide 15-cm-long 10-cm-long ... To demonstrate the airtightness of the chamber during the experimental time frame and to confirm the TVOC signal response obtained by the injection of 1 µL, a blank experiment without injection of acetic acid was performed and a control experiment was performed with injection of acetic acid without MOFs.
[0049] 3.4. Protocol used for Temperature Programmed Desorption (TPD): The protocol used for TPD was adapted from a dynamic adsorption system published by Sayari's group
[42] . Gas flow was controlled using a mass flow meter (stainless steel gas thermal mass flow controller, McMillan 80SD) and the gas path was controlled by a four-way valve. All experiments were performed at slightly above atmospheric pressure (103 kPa). Approximately 90 mg of activated sample (T = 150 °C, D = 15 h) was loaded inside a 6.4 mm inner diameter stainless steel column. The material was incubated at 200 °C for 2 h, 44 cm 3 The system was regenerated under a He flow per minute. Vapor injection was allowed via a 6-way valve. A 50% V / V liquid mixture of organic vapor and water was injected into the system using a 10 μL volume loop connected to the 6-way valve. The injected solution was evaporated using a heating element maintained at 105 °C, and evaporated at 44 cm 3 The column was run / diluted with He at a flow rate of 100 / min. Adsorption took place at room temperature. The column was then heated from room temperature to T=200°C with a heating gradient of 2°C / min. The composition of the column output was recorded as a function of time by a mass spectrometer.
[0050] Example 4: Results of the analysis 4.1 Nitrogen adsorption FIG. 2 shows the resulting nitrogen adsorption isotherms for a) MIL-100(Fe), b) MIL-100(Al), c) MIL-127(Fe), d) MIL-101(Cr) at −196° C.
[0051] 4.2 Acetic acid adsorption FIG. 3 shows acetic acid adsorption isotherms at 25° C. expressed as amount adsorbed per mass for a) MIL-100(Fe), b) MIL-127(Fe).
[0052] 4.3 Propionic acid adsorption Figure 4 shows the propionic acid adsorption isotherm at 25 °C, expressed as the amount adsorbed per mass of MIL-100(Fe). The steepness of the isotherm indicates that propionic acid binds strongly to the MOF in both activated and non-activated samples, which is consistent with the TPD results.
[0053] 4.4 Water adsorption Water adsorption isotherms are shown in Figure 5. This figure shows the water adsorption isotherms at 25°C for activated and non-activated MIL-100(Fe). For MIL-100(Fe), the water isotherm is at 0.1p / p due to the adsorption of water on open metal sites. 0 The first inflection is at 0.20-0.50 p / p due to capillary condensation in the mesopores. 0 The total water capacity at a relative pressure of 0.9 is about 35 mmol / g. Half of the total water capacity of the MOF is at p / p 0 <0.4 (0.35p / p 0 This allows MOFs to have a p / p of less than 0.4. 0 It is confirmed that the MOF adsorbs more than 50% of its total adsorption capacity at the relative pressure.
[0054] 4.5 Removal of acetic acid by MOFs in the presence of 40% RH Figure 6 shows a) a blank experiment without injection of acetic acid (baseline) and with injection of acetic acid without the presence of adsorbent. b) acetic acid concentration profile in the closed chamber after injection of 1 μL of acetic acid at 40% RH in the presence of 50 mg of MIL-100(Fe), MIL-100(Al), MIL-127(Fe) and MIL-101(Cr). For both iron-based and aluminum-based MOFs showing Lewis acid site concentrations higher than 2 mmol / g, the concentration in the chamber after 1 h is similar, so that the acetic acid removal efficiency is comparable. Thus, even in the presence of humidity, the indicated MOFs adsorb significantly larger amounts of acetic acid. Conversely, in the case of the chromium-based MOF, MIL-101(Cr), the number of Lewis acid sites is less than 1 mmol / g, and as a result, the removal of acetic acid from the chamber environment is more poor.
[0055] 4.6 Temperature programmed desorption (TPD) spectra of mixtures of acetic acid and water for MIL-100(Fe) Figure 7 shows the TPD of water and acetic acid from MIL-100(Fe). The first peak of water appears near 66°C, a smaller peak appears near 196°C, and a shoulder appears at the 200°C residence time corresponding to more strongly bound water. An acetic acid peak appears at 196°C, which is 130°C after the first water peak, indicating a higher affinity for the first. Thus, preferential adsorption of acetic acid over the MOF is evident.
[0056] 4.7 Temperature Programmed Desorption (TPD) Spectra of Mixtures of Propionic Acid and Water on MIL-100(Fe) Figure 8 shows the TPD of water and propionic acid from MIL-100(Fe). The first peak for water appears at a residence time of about 95°C, and a smaller peak appears at about 200°C. The propionic acid peak appears only at a residence time of 200°C, indicating a higher affinity for the latter. It is therefore clear that propionic acid preferentially adsorbs to the MOF.
[0057] Example 5: Results Removing low concentrations of acetic acid from indoor air in museums and archives poses serious preservation problems that current adsorbents cannot easily solve due to competitive adsorption of water. In these examples, trimer-based MOFs with different pore sizes, topologies and metal centers were studied to demonstrate that the use of trimer-based MOFs can provide selective adsorbents with high performance in the adsorption of carboxylic acids. This is a result of the presence of Lewis acid sites in these structures that can strongly interact with acid vapors without exhibiting hydrophobicity as required.
[0058] Example 6: Formic acid adsorption TPD analysis repeated using formic acid instead of propionic acid.
[0059] Figure 11 shows the TPD of water and formic acid (50 / 50 vol%) for MIL-100(Fe). The first peak for water appears near 85°C and a smaller peak appears near 200°C. The formic acid peak appears only upon dwell at 200°C, indicating a higher affinity for the latter.
[0060] Figure 12 shows the formic acid adsorption isotherm at 25 °C, expressed as the amount adsorbed per mass of MIL-100(Fe). The steepness of the isotherm indicates that formic acid binds strongly to the MOF in both activated and non-activated samples, which is consistent with the TPD results.
[0061] The same protocol with formic acid gives similar results as with propionic acid. The adsorption isotherms indeed show a sharp increase at low pressure. TPD evidences a first peak associated with water at lower temperatures, and a second peak associated with formic acid at higher temperatures, indicating a stronger formic acid-MOF affinity.
[0062] Example 7: Acetic Acid Breakthrough 60% Relative Humidity Protocol: Dynamic adsorption characterization of acetic acid on powdered MIL-100(Fe) in a packed bed was tested in a setup similar to that shown in Figure S7 from the paper published by Sayari's group
[42] . Gas flow was controlled using a mass flow meter (stainless steel gas thermal mass flow meter, McMillan 80SD) and the gas path was controlled by a 4-way valve. Approximately 25 mg of activated sample (T = 150 °C, t = 15 h) was loaded into a stainless steel column with an inner diameter of 6.4 mm. The sample was then transferred to a 40 cm 3 min -1 The samples were activated in situ for 1 h at a temperature of 150 °C using a nitrogen flow of 1000 Hz (Eurotherm electric laboratory oven with controller, PV accuracy <0.25%, heating lamp 5 °C min -1). During the adsorption experiments, the column was immersed in a water bath at a temperature of 25°C (water bath, accuracy 0.1°C). The column pressure and vent pressure were monitored with a pressure sensor (AA08A Micro-Baratron®, 100 PSI) from MKS and were maintained at isobaric pressure close to atmospheric pressure. The sample was then left to equilibrate with a moisture content controlled at about 60% by passing a nitrogen stream through a bubbler of water (water bath VWR, accuracy 0.1°C) kept at 16.5°C. The gas flow was switched to the acetic acid mixture while the output of the column (downstream column) was recorded by a mass spectrometer (Prismapro, Pfeiffer).
[0063] Results: Dynamic separation performance was tested using MIL-100(Fe) as shown in Figure 13(a). The breakthrough system was at atmospheric pressure and room temperature (25°C). The acetic acid mixture was mixed with N 2 This is equivalent to 498.8 ppm.
number
[0064] where v M =24000cm 3 is the molar volume at T = 25 °C and atmospheric pressure. 3 ) was calculated as follows:
number
[0065] where v sample The maximum signal is used at flow rate (52 cm 3 The area under the curve of the signal acquired by the mass spectrometer is obtained as a function of time when the kinetic energy is set to v / min. background is obtained when repeating the same procedure as for the background measurement (with an empty column). The calculated adsorption volume corresponding to the measurement shown in Figure 13(a) is 7.02 × 10 3 cm 3 The dynamic adsorption amount is the adsorption volume multiplied by the concentration. Considering the mass of the sample used, 28.5 mg:
number
[0066] To compare the amount kinetically adsorbed in the presence of moisture to the amount adsorbed at equilibrium for clean samples, the concentrations of acetic acid must be converted to partial pressures, which can be accomplished by using the non-ideal gas law.
number
[0067] Using pressure p,
number
[0068] Calculation pressure for the concentration used using the ideal gas law is p ideal = 51.5 Pa. This gives Z = 0.715 and p = Z × p ideal = 36.83 Pa. The saturation pressure of acetic acid at 25°C and atmospheric pressure is 2118.36 Pa, so p / p o =0.0174. In the current experiment, 52 cm 3 / min flow rate is not reached, 39 cm 3 The adsorption amount was calculated up to a flow rate of p / p o This means that =0.0174*39 / 52=0.0131 is taken into account.
[0069] The amount adsorbed at equilibrium, corresponding to a partial pressure of 0.0131, is approximately 5.13 mmol g -1 (Acetic acid adsorption isotherm of MIL-100(Fe)), which is in perfect agreement with the value obtained in the breakthrough experiment (Figure 13(b)).
[0070] This means that the presence of water in the gas mixture did not affect acetic acid adsorption, which further supports the previously established conclusion that acetic acid can replace adsorbed water molecules if the presence of water did not impair the kinetic adsorption of acetic acid.
[0071] References 1.United Nations Educational S and CO.Convention Concerning the Protection of the World Cultural and Natural Heritage.http: / / whc.unesco.org / en / conventiontext / .Accessed September 21,2021. 2.Blades N, Oreszczyn T, Bordass B, and Cassar M. Guidelines on pollution control in heritage buildings.Museum Pract.2000;15:1-27. 3.Thickett D, Bradley S, Lee L.Assessment of the Risks to Metal Artifacts Posed by Volatile Carbonyl Pollutants.;1998. 4.V.Kontozova et al.in Proc.Art 2002 7th Int.Conf.Nondestruct.Test.Microanal.Diagnostics Conserv.Cult.Environ.Herit.(Eds.:R.Van Grieken,K.Janssens,L.Van't dack,G.Meersman),University Of Antwerp,Antwerp,2002. 5.Schieweck A,Salthammer T.Indoor air quality in passive-type museum showcases.J Cult Herit.2011;12(2):205-213.doi:10.1016 / j.culher.2010.09.005 6.Al Mohtar A,Pinto ML,Neves A,et al.Decision making based on hybrid modeling approach applied to cellulose acetate based historical films conservation.Sci Rep.2021;11(1):16074.doi:10.1038 / s41598-021-95373-0 7.B.Krupinska,R.Van Grieken,K.De Wael,Microchem.J.2013,110,350. 8.Brokerhof,A.W.;Van Bommel,M.Deterioration of Calcareous Materials by Acetic Acid Vapour:A Model Study;James&James(Science Publishers)Ltd.:London,1996. 9.Tetreault J,Cano E,Van Bommel M,et al.Corrosion of Copper and Lead by Formaldehyde,Formic and Acetic Acid Vapours.Stud Conserv.2003;(3). 10.Gibson LT,Watt CM.Acetic and formic acids emitted from wood samples and their effect on selected materials in museum environments.Corros Sci.2010;52(1):172-178.doi:10.1016 / j.corsci.2009.08.054 11.Prosek T,Taube M,Dubois F,Thierry D.Application of automated electrical resistance sensors for measurement of corrosion rate of copper,bronze and iron in model indoor atmospheres containing short-chain volatile carboxylic acids.Corros Sci.2014;87:376-382.doi:10.1016 / j.corsci.2014.06.047 12.American Society of Heating,Refrigerating and Air-Conditioning Engineers I.Chapter 21-In Heating,Ventilating,and Air-Conditioning:Applications;In:2015 ASHRAE Handbook-Heating,Ventilating,and Air-Conditioning Applications.;2003. 13.Pires J,Pinto ML,Carvalho A,De Carvalho MB.Assessment of Hydrophobic-Hydrophilic Properties of Microporous Materials from Water Adsorption Isotherms.Adsorption.2003;9(4):303-309.doi:10.1023 / A:1026219813234 14.Horcajada P,Salles F,Wuttke S,et al.How linker’s modification controls swelling properties of highly flexible iron(III)dicarboxylates MIL-88.J Am Chem Soc.2011;133(44):17839-17847.doi:10.1021 / ja206936e 15.M.Panchal,F.Nouar,C.Serre,M.Benzaqui,S.Sene,N.Steunou MGM.EP3357929A1-Low Temperature Process For The Synthesis Of MOF Carboxylate Nanoparticles.2018. 16.Garcia Marquez A,Demessence A,Platero-Prats AE,et al.Green microwave synthesis of MIL-100(Al,Cr,Fe)nanoparticles for thin-film elaboration.Eur J Inorg Chem.2012;100(32):5165-5174.doi:10.1002 / ejic.201200710 17.Chevreau H,Permyakova A,Nouar F,et al.Synthesis of the biocompatible and highly stable MIL-127(Fe):From large scale synthesis to particle size control.CrystEngComm.2016;18(22):4094-4101.doi:10.1039 / c5ce01864a 18.Al Mohtar A,Nunes S,Silva J,Ramos AM,Lopes J,Pinto ML.First-Principles Model to Evaluate Quantitatively the Long-Life Behavior of Cellulose Acetate Polymers.ACS Omega.2021;6(12):8028-8037.doi:10.1021 / acsomega.0c05438 19.N.S.Allen,M.Edge TSJ and CVH.Initiation of the degradation of cellulose triacetate base motion picture film.J Photogr Sci.1990;38:54-59. 20.A.Tulsi Ram,D.Kopperl,R.Sehlin,S.Masaryk-Morris JV and PM.The Effects and Prevention of the“Vinegar Syndrome.”In:AMIA,1992. 21.Dupont AL,Tetreault J.Cellulose degradation in an acetic acid environment.Stud Conserv.2000;45(3):201-210.doi:10.1179 / sic.2000.45.3.201 22.Fenech A,Strlic M,Degano I,Cassar M.Stability of chromogenic colour prints in polluted indoor environments.Polym Degrad Stab.2010;95(12):2481-2485.doi:10.1016 / j.polymdegradstab.2010.08.009 23.PINTO,Moises,DA SILVA,Joao,BORDADO,Joao,NUNES,Antonio,BOAVIDA J.International patent application No 2009 / 123484 Al(81)POLYURETHANE FILTERS FOR AIR PURIFICATION(57).2009;2009(October):1-14. 24.Rose M,Bohringer B,Jolly M,Fischer R,Kaskel S.MOF processing by electrospinning for functional textiles.Adv Eng Mater.2011;13(4):356-360.doi:10.1002 / adem.201000246 25.Ostermann R,Cravillon J,Weidmann C,Wiebcke M,Smarsly BM.Metal-organic framework nanofibers via electrospinning.Chem Commun.2011;47(1):442-444.doi:10.1039 / c0cc02271c 26.Ren J,Musyoka NM,Annamalai P,Langmi HW,North BC,Mathe M.Electrospun MOF nanofibers as hydrogen storage media.Int J Hydrogen Energy.2015;40(30):9382-9387.doi:10.1016 / j.ijhydene.2015.05.088 27.M.R.Khan et al.J.Mater.Eng.Perform.2016,25,1276-1283 28.Valekar AH,Lee SG,Cho KH,et al.Shaping of porous metal-organic framework granules using mesoporous ρ-alumina as a binder.RSC Adv.2017;7(88):55767-55777.doi:10.1039 / c7ra11764g 29.Ren J,Musyoka NM,Langmi HW,Swartbooi A,North BC,Mathe M.A more efficient way to shape metal-organic framework(MOF)powder materials for hydrogen storage applications.Int J Hydrogen Energy.2015;40(13):4617-4622.doi:10.1016 / j.ijhydene.2015.02.011 30.Gkaniatsou E,Meng B,Cui F,et al.Moisture-participating MOF thermal battery for heat reallocation between indoor environment and building-integrated photovoltaics.Nano Energy.2021;87(September):106224.doi:10.1016 / j.nanoen.2021.106224 31.Yoon JW,Seo Y-K,Hwang YK,et al.Controlled Reducibility of a Metal-Organic Framework with Coordinatively Unsaturated Sites for Preferential Gas Sorption.Angew Chemie.2010;122(34):6085-6088.doi:10.1002 / ange.201001230 32.Volkringer C,Leclerc H,Lavalley JC,et al.Infrared spectroscopy investigation of the acid sites in the metal-organic framework aluminum trimesate MIL-100(Al).J Phys Chem C.2012;116(9):5710-5719.doi:10.1021 / jp210671t 33.Eubank JF,Wheatley PS,Lebars G,et al.Porous,rigid metal(III)-carboxylate metal-organic frameworks for the delivery of nitric oxide.APL Mater.2014;2(12).doi:10.1063 / 1.4904069 34.Hwang YK,Hong DY,Chang JS,et al.Selective sulfoxidation of aryl sulfides by coordinatively unsaturated metal centers in chromium carboxylate MIL-101.Appl Catal A Gen.2009;358(2):249-253.doi:10.1016 / j.apcata.2009.02.018 35.Jeremias F,Khutia A,Henninger SK,Janiak C.MIL-100(Al,Fe)as water adsorbents for heat transformation purposes-A promising application.J Mater Chem.2012;22(20):10148-10151.doi:10.1039 / c2jm15615f 36.Dedecker K,Pillai RS,Nouar F,et al.Metal-Organic Frameworks for Cultural Heritage Preservation:The Case of Acetic Acid Removal.2018.doi:10.1021 / acsami.8b02930 37.Horcajada P,Surble S,Serre C,et al.Synthesis and catalytic properties of MIL-100(Fe),an iron(III)carboxylate with large pores.Chem Commun.2007;100(27):2820-2822.doi:10.1039 / b704325b 38.Liu Y,Eubank JF,Cairns AJ,et al.Assembly of Metal-Organic Frameworks(MOFs)based on indium-trimer building blocks:A porous MOF with soc topology and high hydrogen storage.Angew Chemie-Int Ed.2007;46(18):3278-3283.doi:10.1002 / anie.200604306 39.Pang M,Cairns AJ,Liu Y,Belmabkhout Y,Zeng HC,Eddaoudi M.Synthesis and integration of Fe-soc-MOF cubes into colloidosomes via a single-step emulsion-based approach.J Am Chem Soc.2013;135(28):10234-10237.doi:10.1021 / ja403994u 40.Ferey C,Mellot-Draznieks C,Serre C,et al.Chemistry:A chromium terephthalate-based solid with unusually large pore volumes and surface area.Science 2005;309(5743):2040-2042.doi:10.1126 / science.1116275 41.Jhung SH,Lee JH,Yoon JW,Serre C,Ferey G,Chang JS.Microwave synthesis of chromium terephthalate MIL-101 and its benzene sorption ability.Adv Mater.2007;19(1):121-124.doi:10.1002 / adma.200601604 42.Serna-Guerrero R,Sayari A.Modeling adsorption of CO2 on amine-functionalized mesoporous silica.2:Kinetics and breakthrough curves.Chem Eng J.2010;161(1-2):182-190.doi:10.1016 / j.cej.2010.04.042 43.(31999L0013)Council directive 1999 / 13 / EC of 11 March 1999.Offical Journal L 085 29 / 03 / 1999 p.0001-0022. 44.Alexandre Vimont,Jean-Michel Goupil,Jean-Claude Lavalley,Marco Daturi,Suzy Surble,Christian Serre,Franck Millange,Gerard Fe rey,and Nathalie Audebrand:Investigation of Acid Sites in a Zeotypic Giant Pores Chromium(III)Carboxylate,J.Am.Chem.Soc.2006,128,3218-3227.
Claims
1. 1. Use of at least one porous metal-organic framework (MOF) material for selective adsorption of volatile organic compounds from a gaseous environment such as air, wherein the volatile organic compounds comprise at least one carboxylic acid group and / or the volatile organic compounds comprise hydroxyl groups, and wherein the MOF material is constructed from trimers of metal octahedra and comprises at least 1 mmol / g of Lewis acid sites interconnected by organic polycarboxylate linkers.
2. The MOF has a p / p of less than 0.4 for a water sorption isotherm at 30° C. 0 2. The use according to claim 1, wherein the MOF adsorbs more than 50% of its total adsorption capacity at a relative pressure.
3. 3. Use according to claim 1 or 2, wherein the MOF material metal centre is selected from Fe, Al, Ti, Mn, V, Sc, Mn, Cr and mixtures thereof, preferably Fe, Al and mixtures thereof.
4. 4. Use according to any one of claims 1 to 3, wherein the MOF material comprises Lewis acid sites constructed from trimers of metal octahedra and interconnected by organic polycarboxylate linkers in a concentration of at least 1.5 mmol / g, preferably at least 2 mmol / g or at least 2.5 mmol / g.
5. The MOF material is 50 m 2 / g, preferably 100m 2 / g, the specific surface area being determined by the N 2 5. Use according to any one of claims 1 to 4, as assessed by the BET model from isotherms.
6. 6. The use according to claim 1 , wherein the MOF material has an average pore size of more than 0.5 nm.
7. The organic polycarboxylate linker is preferably selected from dicarboxylic, tricarboxylic or tetracarboxylic acids, ・Halo group, -OH, -NH 2 and -NO 2 C optionally having one or more substituents selected from 6 ~C 24 an aromatic polycarboxylate linker, and ・Halo group, -OH, -NH 2 and -NO 2 C optionally having one or more substituents selected from 4 ~C 16 Polycarboxylate Aliphatic Linkers 7. The use according to any one of claims 1 to 6, selected from the group comprising:
8. Said C 6 ~C 24 The aromatic polycarboxylate linker may be selected from the group consisting of terephthalate, 1H-pyrazole-3,5-dicarboxylate, 2,5-furandicarboxylate, naphthalene-2,6-dicarboxylate, biphenyl-4,4'-dicarboxylate, benzene-1,2,4-tricarboxylate, benzene-1,3,5-tricarboxylate, benzene-1,3,5-tribenzoate, benzene-1,2,4,5-tetracarboxylate, 3,3',5,5'-tetracarboxylate diphenylmethane, naphthalene-2,3,6,7-tetracarboxylate, naphthalene-1,4,5,8-tetracarboxylate, biphenyl-3,5,3',5'- 8. The use according to claim 7, wherein the terephthalate is selected from the group consisting of azobenzenetetracarboxylate, 2-chloroterephthalate, 2-bromoterephthalate, azobenzenedicarboxylate, azobenzenetetracarboxylate, 2,5-thiophenedicarboxylate, 2-aminoterephthalate, 2-nitroterephthalate, 2,5-dihydroxyterephthalate, 2,5-pyrazinedicarboxylate, azobenzene-4,4'-dicarboxylate, 3,3'-dichloro-azobenzene-4,4'-dicarboxylate, 3,3'-dihydroxy-azobenzene-4,4'-dicarboxylate, 3,5,3',5'-azobenzenetetracarboxylate and mixtures thereof.
9. Said C 4 ~C 16 The polycarboxylate aliphatic linker is preferably selected from fumarate, succinate, glutarate, muconate, adipate and mixtures thereof. 4 ~C 16 8. The use according to claim 7, which is a polycarboxylate alkyl linker.
10. The MOF material is selected from MIL-88A(Fe), MIL-88B(X)(Fe), where X is Br, NH 2 , Cl, NO 2 10. The use according to any one of claims 1 to 9, wherein the cations are selected from the group consisting of MIL-100 (Fe, Al), MIL-127 (Fe), 2OH and COOH, and mixtures thereof, more preferably selected from MIL-100 (Fe, Al), MIL-127 (Fe), and mixtures thereof.
11. Use according to any one of claims 1 to 10 in air quality applications, preferably for art conservation, indoor air purification systems such as HEPA air filters, adsorbent purifiers, kettle filters, fet filters, honeycomb filters or air conditioning filters, outdoor air purification systems such as gas masks, nose filters, adsorption columns or chimney filters, cosmetic applications such as deodorants, anti-odour shampoos, hygiene protection products, wipes or diapers.
12. 12. Use according to any one of claims 1 to 11, wherein the gaseous environment is air, said gaseous environment preferably having a relative humidity of between 20% and 80%, preferably between 40% and 60%, and preferably having a temperature of between 10 and 180°C, preferably between 15 and 100°C, more preferably between 15 and 50°C.
14. 14. Use according to any one of claims 1 to 13, wherein the volatile organic compounds are selected from VOCs containing a carboxylic acid function, preferably selected from acetic acid, formic acid, acrylic acid, propionic acid, isovaleric acid, propiolic acid, butyric acid, isobutyric acid, crotonic acid, methacrylic acid, diacetic acid, butynedioic acid, valeric acid, 2-methylbutanoic acid, pivalic acid, hexanoic acid, 2,3-trimethylbutanoic acid, 3-methylhexanoic acid, 2-ethyl-2-methylbutanoic acid, 3-ethylpentanoic acid, 3,3-dimethylpentanoic acid, 2,4-dimethylpentanoic acid, 2,3-dimethylpentanoic acid, 2-methylbutanoic acid and mixtures thereof.
15. The volatile organic compounds are selected from VOCs containing hydroxyl functionality, preferably monoalcohols, preferably linear, branched or cyclic C 1 ~C 10 15. The use according to any one of claims 1 to 14, wherein the alcohol is selected from monoalcohols and mixtures thereof, more preferably selected from methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, pentanol, isopentanol, hexanol, isohexanol, and mixtures thereof.
16. 16. Use according to any one of the preceding claims, wherein the concentration of said volatile organic compounds in said gaseous environment is at least 40 ppb, preferably at least 400 ppb, more preferably at least 1 ppm.
17. 17. The use according to any one of claims 1 to 16, wherein the at least one MOF material is embedded in the form of a powder, granules, pellets, extrudates, monoliths, foamed materials, polymers or fibers, or is in the form of a composite coated on the surface of a polymeric material, a paper sheet, a fiber or a metal.
18. 18. Use according to any one of claims 1 to 17, wherein at least one MOF material or at least one MOF in the form according to the claims is comprised in an apparatus selected from an air purifier, a sensor, an adsorption column, a filter, a respirator, an adsorption tower, a hygiene protection product, a wipe or a diaper.
